Mengatasi Kesalahan Penulisan Bilangan Dua Digit Pada Siswa Kelas II Sekolah Dasar Dengan Media Puzzle Angka - Hesti Zulianti; Tiurlina; Fitri Alfarisa (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Mathematics in elementary schools includes three branches of knowledge that are taught in the field of mathematics studies, including arithmetic, algebra, and geometry. Most students who have just entered school already recognize symbols as well as how to name a number. They are able to number sequentially, although there are still many who do not really know how to write and recognize number symbols properly and correctly. Based on the results of interviews with teachers in class II A SD Negeri Panyirapan 02, from the total number of students, namely 36 people, 5 students have been found who have problems writing two-digit number symbols. Referring to the facts in the field, this study aims to determine the causes of students experiencing errors in writing two-digit numbers and find out how the application and success of number puzzle media as an effort to overcome existing problems. The research approach used is a qualitative approach, using case study methods through in-depth interviews, observations, tests, and documentation. From the results of the study, it has been found that there are several factors that can cause learning difficulties that can result in errors in writing two-digit numbers, namely internal factors and external factors. Then, in the application of number puzzle media as an effort to overcome existing problems, students are directly involved in using the media so that they are very enthusiastic in participating in learning. With an increase in the value obtained by students, namely when the pre-test the lowest score that students get is 65, while during the post-test the lowest score that students get is 80, then the average student is wrong in answering the number of questions about counting, while for the number of questions about writing number symbols can be answered correctly by all students. Referring to the results obtained, the number puzzle media can be a solution to overcome students' problems in writing number symbol errors.